Analysis of Renewal Team Negotiation Strategy in Achieving Consumer Deals (Case Study at PT. Moka Teknologi) - Dwi Hariana Pane; Pri Hermawan (Budapest International Research and Critics University, 2022)
In the business world, competition between companies that have the same type of sales is common. The number of food entrepreneurs currently encourages application companies to make innovations in the online cashier system which will help FNB entrepreneurs control income and monthly reports on their businesses. PT MokaPOS is a service company that provides cashier-based applications. Where currently the customer has reached 40,000. The high competition in this application makes Mokapos continue to make developments in the application. However, it is not enough because with the number of customers they already have, how to keep their customers using MokaPOS.The Renewal team is tasked with retaining customers by negotiating when offering price quotes for their MokaPOS account extensions in this case, to find out how to get customer deals this study uses sem pls analysis to find out how to get customer deals.